Renewable energy consumption and economic growth in OECD countries: A nonlinear panel data analysis. (15th September 2020) - Wang, Qiang; Wang, Lili
Abstract: What impact will increasing renewable energy consumption have on economic growth? What is the direction or magnitude of the impact and the determinants behind it? Existing research on the relationship between renewable energy and economic growth focuses on the linear relationship, whereas ignoring the non-linear relationship between them. In this study, the nonlinear relationship between renewable energy and economic growth in OECD countries was investigated by developing panel threshold regression models. Non-renewable energy intensity, urbanization level and per capita income are used as threshold variables to explore the internal mechanism of renewable energy for economic development. Three panel threshold models are developed based on these three threshold variables. The results show that the effect of renewable energy consumption on economic growth is positive, which indicates that increased renewable energy consumpiotn contributes to economic growth. In addition, this positive relationship changes as the threshold value changes, which means that the role of increasing renewable energy consumption to promote economic development is nonlinear. In other words, if the EU countries increase their renewable energy consumption by more than a certain amount (threshold value), the role of renewable energy consumption in promoting economic development is more significant. Highlights: Analyzing renewable energy and economic in OECD countries. The fixed-effect model and non-linear threshold model are employed. Three factors were used as threshold variables to explore the mechanism. Renewable energy has a threshold effect on economic growth.